2012
DOI: 10.4315/0362-028x.jfp-11-260
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Performance of a Food Safety Management System in a Food Service Operation

Abstract: The microbiological performance of a food safety management system in a food service operation was measured using a microbiological assessment scheme as a vertical sampling plan throughout the production process, from raw materials to final product. The assessment scheme can give insight into the microbiological contamination and the variability of a production process and pinpoint bottlenecks in the food safety management system. Three production processes were evaluated: a high-risk sandwich production proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
3
26
1
Order By: Relevance
“…A poor result (level 1) was defined as when legal criteria or guideline values were exceeded and improvements were needed for multiple control activities of the FSMS. The total sum of these levels gave the MSLP score (33,44). The maximum MSLP score for CSL1 through CSL6 was 18 (six microbiological parameters with a maximum MSLP score o f 3 for each) and that for CSL7 was 15 (five microbiological parameters with a maximum MSLP score of 3 for each).…”
Section: Selection Of Microbiological Parametersmentioning
confidence: 99%
“…A poor result (level 1) was defined as when legal criteria or guideline values were exceeded and improvements were needed for multiple control activities of the FSMS. The total sum of these levels gave the MSLP score (33,44). The maximum MSLP score for CSL1 through CSL6 was 18 (six microbiological parameters with a maximum MSLP score o f 3 for each) and that for CSL7 was 15 (five microbiological parameters with a maximum MSLP score of 3 for each).…”
Section: Selection Of Microbiological Parametersmentioning
confidence: 99%
“…From the challenge test results it was noted that the indigenous lactic acid bacteria also showed significant outgrowth after 13 days storage although they could not inhibit the growth of (artificially inoculated) L. monocytogenes. The lactic acid bacteria dominated the microbiota on the cooked meat product but at the expiry data numbers present were (just) below the 7.0 log CFU/g (at 4 C and 7 C) and thus near but not exceeding the threshold level for causing adverse sensorial properties of the product (Lahou, Jacxsens, Daelman, Van Landeghem, & Uyttendaele, 2012). As such the expiry data was appropriately set with respect to the spoilage organisms and did not lead to a deteriorated product throughout the recommended shelf life.…”
Section: Stakeholder Opinions On Shelf Life Labelsmentioning
confidence: 99%
“…Several studies conducted internationally provide definitive evidence that insufficient decontamination actions are a primary cause of pathogenic contamination. Food handling and personal hygiene research has shown the most common factors in pathogenic contamination for food service operations to be: improperly cleaned or not cleaned knives, faucets, serving utensils, and cutting boards; crosscontamination between use with different products; and barehanded food contact [29][30][31]. Even when gloves are worn they are often unchanged between food and customer contact with the result that the gloves themselves are found over time to be the cause of pathogen transfer [32].…”
Section: Literature Reviewmentioning
confidence: 99%